Pengaruh Kompensasi Finansial Dan Nonfinansial Terhadap Prestasi Kerja Karyawan PT. Semen Baturaja (Persero) Tbk Palembang - Desi Tri Utami; Amirudin Syarif (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
The purpose of this study was to determine and explain the effect of financial compensation and non-financial compensation on the work performance of PT. Semen Baturaja (Persero) Tbk. The subjects in this study were all marketing employees of PT. Semen Baturaja (Persero) Tbk, totaling 150 people. Then obtained a sample of 60 people, namely permanent employees of PT. Semen Baturaja (Persero) Tbk by using a purposive sampling technique. Data obtained through distributing questionnaires, observing, and interviews. The data analysis techniques applied by the researchers were validity, reliability, classical assumptions, multiple linear regression analysis, and hypothesis testing. From the results of the tests that have been carried out, it is found that financial and non-financial compensation significantly affects employee performance.